Objectively measured physical environmental neighbourhood factors are not associated with accelerometer-determined total sedentary time in adults - Sofie Compernolle; Katrien De Cocker; Joreintje D. Mackenbach; Femke Van Nassau; Jeroen Lakerveld; Greet Cardon; Ilse De Bourdeaudhuij (BMC, 2017)
Abstract Background The physical neighbourhood environment may influence adults' sedentary behaviour. Yet, most studies examining the association between the physical neighbourhood environment and sedentary behaviour rely on self-reported data of either the physical neighbourhood environment and/or sedentary behaviour. The aim of this study was to investigate the associations between objectively measured physical environmental neighbourhood factors and accelerometer-determined total sedentary time in adults. Methods In total, 219 Dutch and 128 Belgian adults (mean age ± SD: 55.8 ± 15.4 years) were recruited between March and August 2014 as part of the European SPOTLIGHT project. Physical environmental neighbourhood factors, grouped into eight domains, i.e. walking, cycling, public transport, aesthetics, land use mix, grocery stores, food outlets and recreational facilities, were assessed using the SPOTLIGHT Virtual Audit Tool. Sedentary time was collected using ActiGraph GT3X+ accelerometers. General linear mixed models were conducted to examine associations between physical environmental neighbourhood factors and total sedentary time. Results Participants were sedentary, on average, for 542.9 min/day (SD: 84.3), or 9.1 h/day. None of the examined physical environmental neighbourhood factors were significantly related to total sedentary time. Conclusions Our findings do not support associations of objectively measured physical environmental neighbourhood factors with adults' objectively sedentary time in Dutch and Belgian adults. More research on sedentary behaviours in settings such as the home and work setting is needed to examine the influence of more specific physical environmental factors on these context-specific sedentary behaviours.